2013
DOI: 10.1158/1078-0432.ccr-12-3497
|View full text |Cite
|
Sign up to set email alerts
|

Margin-Infiltrating CD20+ B Cells Display an Atypical Memory Phenotype and Correlate with Favorable Prognosis in Hepatocellular Carcinoma

Abstract: Purpose: The role of infiltrating B cells in hepatocellular carcinoma has been overlooked for many years. This study is aimed to delineate the distribution, prognostic value, and functional status of B cells in human hepatocellular carcinoma.Experimental design: Immunohistochemistry was used to investigate the distribution and clinical significance of infiltrating CD20þ B cells in a series of 120 patients with hepatocellular carcinoma. The results were further tested in an independent series of 200 patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 53 publications
9
161
2
2
Order By: Relevance
“…We also noted that a portion of transferred TIM-4 + B cells infiltrate the tumor, suggesting that Be1 cells may exert at least part of their effector function locally. Of note, tumor infiltration with B cells and B cell: CD8 + T cell interactions within ovarian and various other cancers are associated with improved prognosis (19, 52, 53). Interestingly, we did find occasional TIM-4 + B cells that were closely associated with CD8 + TILs (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that a portion of transferred TIM-4 + B cells infiltrate the tumor, suggesting that Be1 cells may exert at least part of their effector function locally. Of note, tumor infiltration with B cells and B cell: CD8 + T cell interactions within ovarian and various other cancers are associated with improved prognosis (19, 52, 53). Interestingly, we did find occasional TIM-4 + B cells that were closely associated with CD8 + TILs (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these last functions, Nielsen et al observed in ovarian cancer that tumor-infiltrating CD20 + B cells were often found in close proximity to CD8 + T cells, expressed MHC Class I, MHC Class II, CD80, and CD86 molecules, and that the presence of combined CD20 + and CD8 + lymphocytes was associated with prolonged patient's survival . The expression of surface markers' characteristic of APC by tumor-infiltrating B cells was also described in primary lung cancer (Yasuda et al, 2002) and in hepatocellular carcinoma (Shi et al, 2013). Finally, few studies suggested that some tumorinfiltrating B cells could act as true killer cells, through the expression of granzyme B and TRAIL (Shi et al, 2013), or in a Fas Ligand-dependent manner (Tao et al, 2015).…”
Section: Role Of B Cellsmentioning
confidence: 95%
“…The expression of surface markers' characteristic of APC by tumor-infiltrating B cells was also described in primary lung cancer (Yasuda et al, 2002) and in hepatocellular carcinoma (Shi et al, 2013). Finally, few studies suggested that some tumorinfiltrating B cells could act as true killer cells, through the expression of granzyme B and TRAIL (Shi et al, 2013), or in a Fas Ligand-dependent manner (Tao et al, 2015).…”
Section: Role Of B Cellsmentioning
confidence: 95%
“…B lymphocytes could also influence T cell polarization and functions by secreting type 1 (IL-12, IFN-γ), type 2 (IL-4, IL-13), and immune suppressive (IL-10, IL-35, TGF-β) cytokines. Production of IL-12 and IFN-γ by intra-tumoral B lymphocytes in hepatocellular carcinoma indicates a putative role of these cells in the induction and/or the amplification of a strong cellular immune response (30). However, tumor-infiltrating B cells could also act as negative regulators of the anti-tumor response, as already discussed for the role of IgA produced locally (see above).…”
Section: Tls As a School For Adaptive Immune Cellsmentioning
confidence: 99%